2001
DOI: 10.1002/1521-3765(20010504)7:9<1881::aid-chem1881>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Oxalate Crystals in Tomato and Tobacco Plants: Morphology and in Vitro Interactions of Crystal-Associated Macromolecules

Abstract: Plants form calcium oxalate crystals with unique morphologies under well-controlled conditions. We studied the morphology of single calcium oxalate monohydrate (whewellite) crystals extracted from tomato and tobacco leaves. These crystals have a pseudotetrahedral shape. We identified the (101), (101) or (102), (110), and (hk0) faces as stable faces. The morphology is chiral with unique handedness. We also show that calcium oxalate monohydrate crystals isolated from tomato, tobacco, and bougainvillea leaves con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 48 publications
2
97
0
1
Order By: Relevance
“…Because these acidic proteins are homochiral, they were even found to induce chiral shapes of unique handedness into otherwise achiral minerals. As an example stands calcium oxalate crystals extracted from tomato and tobacco leaves with pseudotetrahedral shape [193].…”
Section: Diastereomers and Diastereomeric Recognitionsupporting
confidence: 55%
“…Because these acidic proteins are homochiral, they were even found to induce chiral shapes of unique handedness into otherwise achiral minerals. As an example stands calcium oxalate crystals extracted from tomato and tobacco leaves with pseudotetrahedral shape [193].…”
Section: Diastereomers and Diastereomeric Recognitionsupporting
confidence: 55%
“…AFM images of the surfaces of the washed COD crystals were flat and devoid of any features associated with adsorbed poly(acrylic acid), which typically is evident as irregular lumps when adsorbed on CaOx surfaces. Powder x-ray diffraction of COD crystals grown by this method confirmed the existence of COD, and no unusual features were observed that would suggest inclusion of poly(acrylic acid) in the crystals, as has been suggested for proteins and amino acids in COM (14,15). Topographical and lattice images of the crystal surfaces were acquired with commercial Si 3 N 4 cantilever tips in aqueous solutions containing 0.11 mM CaOx.…”
Section: Methodsmentioning
confidence: 99%
“…27 For the preparation of metal-doped COM, the metal salts [CuSO4*5H2O (Merck, Darmstadt, Germany), CdCl2*2.5H2O (Sigma-Aldrich, St.…”
Section: Calcium Oxalate Synthesismentioning
confidence: 99%